Anthropolinguistic Study of The Ngantukang Ajang Ritual - Komang Astiari (CV. AFDIFAL MAJU BERKAH, 2026)
This study examines the local ritual of “Ngantukang ajang” conducted in Bila Bajang, Buleleng, Bali from the anthropolinguistics and semiotics perspective whereas meaning is produced, structured, and communicated through non-verbal semiotic resources. Unlike previous studies that focused on religious and cultural values, this research emphasized on the ritual as semiotic system like objects, movements, and arrangements. The qualitative method was applied by noting down the ritual sequences, material objects, and patterns of participation. The finding showed that “ngantukang ajang” is a process which semiotically redistributes ritual entitlements (rice and “sesari”, a monetary offerings) received by the former “kelihan subak” (the head of water distribution). Three stages were done namely “matur piuning”, “ngeragaang”, and the peak ceremony. It reflects a transformation of social identity and detachment shown from reconfiguration of the deceased from an active socio-political leader into ancestral presence. The semiotic resources form a non-verbal discourse communicating principles of reciprocity, and obligation.